2009
DOI: 10.1016/j.immuni.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Cellular Site of Glycolipid Loading Control the Outcome of Natural Killer T Cell Activation

Abstract: SummaryCD1d-restricted natural killer T cells (NKT cells) possess a wide range of effector and regulatory activities that are related to their ability to secrete both T helper 1 (Th1) cell- and Th2 cell-type cytokines. We analyzed presentation of NKT cell activating α galactosylceramide (αGalCer) analogs that give predominantly Th2 cell-type cytokine responses to determine how ligand structure controls the outcome of NKT cell activation. Using a monoclonal antibody specific for αGalCer-CD1d complexes to visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
239
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(259 citation statements)
references
References 44 publications
(50 reference statements)
16
239
0
1
Order By: Relevance
“…5B). Staining with the L363 mAb, which detects CD1d-α-GalCer complexes (14,17), confirmed the increased appearance of complexes on the plasma membrane at very early time points (Fig. 5C) and their reduced persistence at late time points (24 h) (Fig.…”
Section: Facilitated Presentation Of Lipid Antigens In Cd1e Transgenisupporting
confidence: 53%
See 1 more Smart Citation
“…5B). Staining with the L363 mAb, which detects CD1d-α-GalCer complexes (14,17), confirmed the increased appearance of complexes on the plasma membrane at very early time points (Fig. 5C) and their reduced persistence at late time points (24 h) (Fig.…”
Section: Facilitated Presentation Of Lipid Antigens In Cd1e Transgenisupporting
confidence: 53%
“…CD1e might directly influence the number of CD1d-antigen complexes available over time, which has been shown to affect the type of cytokines released (12)(13)(14). To test this possibility, antigen-pulse experiments were performed to compare the time required for the generation of CD1d-antigen stimulatory complexes.…”
Section: Cd1e Effects On Exogenous Glycolipid Antigen Presentation Tomentioning
confidence: 99%
“…In particular, CD1b and CD1d are relatively resistant to exogenous antigen loading at neutral pH conditions normally found in the secretory pathway (3)(4)(5)(6). They more rapidly exchange antigens at pH 4-6, which is characteristic of the late endosomal or lysosomal environment (7,8). The differing pH requirements for antigen loading, combined with enrichment of endogenous lipids in the secretory pathway and exogenous lipids endosomes, are coalescing into a two-step model of lipid antigen presentation.…”
mentioning
confidence: 99%
“…Second, upon reaching the endosomes by recycling or direct routes, the acidic pH facilitates the unfolding or untethering of the parallel α-helices that normally restrict ligand access to the groove (3-6). Increased groove access promotes both unloading of the initially bound endogenous lipids and subsequent capture of the exogenous lipids delivered by infection, lipid transfer proteins, or receptor-mediated uptake (8,10).…”
mentioning
confidence: 99%
“…Despite high homology, the four saposins have different lipid specificities, as demonstrated by the phenotype of patients with selective deficiency of individual molecules (53). We limited our study to the role of saposin B, because evidence from our own works and from the literature (8,11,32) suggested its dominant role in loading soluble lipids onto CD1d molecules. We determined the binding affinity of saposin B to a radiolabeled version of ThrCer at pH5 and pH7 (1.8 μM and 4.5 μM, respectively), and observed that it reached a plateau when saposin B was present in molar excess.…”
Section: Discussionmentioning
confidence: 99%